Coach behaviours and practice structures in youth soccer: Implications for talent development - Cushion, C.; Ford, P. R.; Williams, A. M. (Journal of Sports Sciences, 2012)
Coaches are central to talent development in youth soccer and what they say and do impacts on players? achievements and well-being. Researchers have systematically observed coach behaviour and practice activities within this setting (i.e. "what coaches do"). We review this research in light of contemporary discussion that highlights a potential "theory-practice" divide. Our main example focuses on the discrepancy between coaching behaviour and research from the sports science sub-discipline areas of motor learning and skill acquisition that relate to how best to design practice sessions and provide instruction (i.e., "what coaches should probably do"). The underlying reasons for this discrepancy are discussed and recommendations made to address this disparity in research, education and coach behaviours.